The digital inclusion of blacks in Brazil - Carlos Lopes Fernandes, João; de Oliveira, Daniel; Maria Martins de Souza, Mônica (Seven Editora, 2023)
This article seeks to identify the digital inclusion level in the Afro-descendant community and the advancement of public policies in this regard. Another important factor is how the use of information technology and used in school routine communications can provide African descent opportunities for access to the "information age/computerization". Digital inclusion is directly linked to socio-economic exclusion, so along with education; it is one of the pillars of social sustainability. It notes that this reality is present in third-world countries, and in the case of Brazil where racial issues are disguised as a racial democracy, it becomes more difficult to solve this problem, because the Afro-descendant population, low-income is excluded era digital. From these findings, we find that the digital divide not only includes access to the Internet, but something much broader and that the fundamental rights to information and communication are constrained because of the digital divide. We also identified that the Federal Constitution of 1988, the principle of material equality based on promoting digital inclusion and uses tax exemption as a legitimate mechanism to implement inclusive public policies in a way that involves all federal levels and their respective tax species. DOI: https://doi.org/10.56238/devopinterscie-174